The QRS complex during myocardial ischemia. An experimental analysis in the porcine heart. - Holland, R P (1976)
Although ST segment deflections have been widely utilized as a means of assessing the degree of underlying ischemic injury, the relationship of QRS complex alterations to the ischemic process is poorly understood. In this study we made a beat-to-beat analysis of the QRS complex in terms of ventricular activation time (CT) and R wave voltage (V) in the acutely ischemic porcine myocardium and analyzed the relationship of these responses to changes in the area of ischemic involvement, altered myocardial energy demands, and plasma [K+]0 levels. With the onset of ischemia the QRS complex underwent a specific and reproducible biphasic sequence with an initial decrease in CT and V indicating a transient increase in the conduction velocity of the ischemic tissue. Subsequently both CT and V returned briefly to control and then increased dramatically, now indicating a marked decrease in conduction velocity. The time when CT first began to increase (Tc) was shortened by enlarging the area of ischemia or after an inotropic intervention and was lengthened by decreasing the area of ischemia or with administration of propranolol. Moreover Tc was found to be inversely proportional to plasma [K+]0 in the range 3.4-8.8 mM, above which the initial decrease in CT and V was no longer present. We conclude that this biphasic sequence of QRS alterations in early myocardial ischemia is attributable to a progressive leakage of potassium out of the ischemic cells which in turn alters both the time-course and transmural pathway of the activation process through the ischemic tissue. These changes are related to both inotropic state and the area of ischemic involvement.